The enhancement effort of chili’s resistance to water stress & disease by application of priming technique - Roektiningroem, Ekosari; Djukri, Djukri (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2014)
This research aims to know the influence of chili’s seed priming on improving germination, growth, and development in the field, before, during, and after stress conditions (water stress and disease). Priming is a technique of seed pretreatment with osmoticum solution or moist solids, which allows slow inbibition; thus radicals emergence and growth are prevented. It is a simple and easy technique to apply, which can increase the germination, and performance or vigour in a broad spectrum. Implementation is in three trials, each trial consisting of 2 stages. The first stage on the early experiment was priming (priming treatment with 4 days incubation and priming test), and the second stage was the germination (germinating the seed that has been treated by priming and germination test). The first stage on the further experiment is priming and the second stage were growth and development test before, during, and after the stress conditions. The results showed that seed priming treatments can maintain and improve the quality of seeds, and increase germination, both germination percentage and germination rate, as well as enhance the growth of plant height and total leaves of Chili at age 2 wat (weeks after transplanting). Key word: priming technique, disease, water stress, plant resistance